2014
DOI: 10.1055/s-0034-1383000
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cytochrome P450 2C9 Expression and Activity In Vitro by Allyl Isothiocyanate

Abstract: The growing interest in the use of natural herbal products and dietary supplements to treat and prevent diseases raises the question of medicinal drug safety. Allyl isothiocyanate, a hydrolysis product of a glucosinolate, sinigrin, has multiple beneficial properties, and based on this fact, allyl isothiocyanate-containing dietary supplements have been developed. To date, no studies of the effects of this compound on the cytochrome P450 2C9 have been reported. In this study, we found that allyl isothiocyanate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…As previous studies reported, CYP2E1 and CYP2C9 play a vital role in the metabolism of many drugs (He et al 2009;Lim et al 2014;Xu et al 2017;Bedada and Neerati 2018). There are also many drugs inhibiting the activity of CYP2E1 and CYP2C9 (Pan et al 2010;Jiang et al 2016;Liu et al 2017;Hao et al 2018), and we get similar results in the study of CEP.…”
Section: Discussionsupporting
confidence: 82%
“…As previous studies reported, CYP2E1 and CYP2C9 play a vital role in the metabolism of many drugs (He et al 2009;Lim et al 2014;Xu et al 2017;Bedada and Neerati 2018). There are also many drugs inhibiting the activity of CYP2E1 and CYP2C9 (Pan et al 2010;Jiang et al 2016;Liu et al 2017;Hao et al 2018), and we get similar results in the study of CEP.…”
Section: Discussionsupporting
confidence: 82%
“…CYP2C9 is also playing an important role in the metabolism of many drugs [25]. Our study showed that cynaroside competitively inhibited human liver microsomal CYP2C9 activity.…”
Section: Discussionmentioning
confidence: 52%
“…However, the results also indicated that cynaroside is a timedependent inhibitor for CYP3A4 with K inact /K I value of 0.049/11.62 μmol/L -1 min -1 , which revealed that cynaroside would inhibit the activity of CYP3A4 with increase of preincubation time of concentration. Therefore, in order to avoid adverse drug interactions, cynaroside should not be used with other drugs metabolized by CYP3A4, such as amiodarone, acetaminophen, cyclosporin A, lansoprazole, felodipine, meloxicam, and ketoconazole [25].…”
Section: Discussionmentioning
confidence: 99%
“…CYP2C9 also plays an important role in the metabolism of many drugs (Lim et al. 2014). Our study showed that KF competitively inhibited human liver microsomal CYP2C9 activity.…”
Section: Discussionmentioning
confidence: 99%